Rosenkranse i grave: Gravskikkens baggrund, datering og perspektiver - Koch, Hanne Dahlerup (Hikuin, 2000)
Rosaries in graves. The backround, dating, and perspectives of the grave custom By Hanne Dahlerup Koch The subject of the article is the use of rosaries as grave gifts. The author explains the background for the development of the rosary prayers with an emphasis on its Danish history. Danish religious literature and wall-paintings from the Middle Ages are included in the review. Following a critical analysis of the basis on which arm position B has been dated, the author concludes that rosaries were not used as grave gifts until the 1400s and later, in spite of the fact that some have been found in graves of arm position B and A. The probable explanation to this is that the arm position chronology was disintegrated already before the reformation, and not, as is commonly thought, after the reformation. In the light of a survey of rosary graves found within present Denmark the author argues that the observance movement, which in Denmark was especially active within the Franciscan order , was of great significance to the introduction of the rosary prayers in Denmark, whereas the Dominican order – as opposed to common belief – apparently played no significant part in this. Further it is argued that people of the late Middle Ages preferred to be buried somewhere else than in the parish churchyard, for instance in monastery churchyards or in churchyards of pilgrim chapels or pilgrim churches. This theory will have vast consequences for the interpretation of archaeological and anthropological material from excavated medieval churchyards.